The effect of superplasticizer (SP) on the workability and skid resistance of geopolymer concrete (GPC) containing high calcium precursor (HCP) / A’lia Sofea Shamsol … [et al.] - Shamsol, A’lia Sofea; Arshad, Mohd Fadzil; Mohd Apandi, Nazirah; Ahmad Zailani, Warid Wazien; Khairul Izwan, Khairul Nazhan (Research Management Institute (RMI), 2023)
A superplasticizer (SP) is one of the admixtures that may be used to improve the workability of concrete. However, its effects on geopolymer concrete (GPC) have yet to be well known or published, especially regarding its skid resistance and workability performance. This research aims to study the impact of the superplasticizer on the skid resistance and workability of geopolymer concrete containing high calcium precursor (HCP) in different proportions of SP, which are 0, 0.5, 1.0, 1.5 and 2.0 % by the weight of the HCP. Seven mix designs were produced: 1 conventional concrete mix, 5 geopolymers concrete mix, and 1 bituminous cold-mix asphalt mix. Slump flow and skid resistance tests were performed in this study. A skid resistance test is achieved using a British Pendulum Tester (BPT) on a 220 mm x 220 mm x 50 mm rectangle. This study found that the effect of SP on skid resistance is insignificant. However, the skid resistance of all GPC mix designs is higher than CC and asphalt mix. The workable flow of geopolymer concrete containing HCP and 0 - 2 % SP was 118-123 mm. However, less than 2 % of SP is given an insignificant difference. The optimum mix design of GPC is mix design GPC with an added 2 % SP (M6) that gives a high workability compared to other GPC mix designs and good skid resistance of 95 BPN. This study also found that workability correlates with skid resistance. The higher the spreading width value, the smaller the skid resistance value. In other words, the higher the flowability value, the less rough the sample surface.